RIPASA score or Alvarado score: diagnosing acute appendicitis - Parmeshwar, Talabadi; Ghag, Geeta Sandeep; Nandu, Vipul Versi (International Surgery Journal, 2021)
Background: Appendicitis is a much studied about topic since the early years. Even with the advances in imaging techniques, appendicitis still relies upon clinical examination as a main resort of diagnosis. To aid this, several scoring systems have been developed taking into account various symptoms, signs and some basic laboratory investigations. Many studies have been done worldwide to check the sensitivity and specificity of each of these clinical scoring systems in the diagnosis of acute appendicitis. Though the most famous one is the Alvarado scoring system, there is none universally accepted scoring system used for diagnosis so far. Methods: 100 patients with RIF pain and who were suspected of acute appendicitis were evaluated for a period of 24 months. Evaluation was done with regards to RIPASA and Alvarado scoring in all these patients. All the results of both the scoring systems were reported and correlated with histopathological findings. Statistical test were applied to calculate the p value for the association between the variables of studied. Results: There was definitive agreement that both the scoring systems are positively correlating with each other with respect to the diagnosis of the disease (p value 0.0001). The difference in diagnostic accuracy of 25% between the RIPASA score and Alvarado score was statistically significant (p<0.0001). On analysis with chi-square test, both scores are significant at level 1 (p=0.0001). But RIPASA score has higher sensitivity and diagnostic value when compared to Alvarado score. Conclusions: The use of RIPASA scoring would help in decreasing the unwarranted patient admissions and also expensive radiological investigations.